TEKNIK WDEP SYSTEM DALAM MENINGKATKAN KETERAMPILAN BELAJAR SISWA UNDERACHIEVER - Adiputra, Sofwan (JURNAL FOKUS KONSELING, 2016)
Not all students have the same ability as their intellegence, it happened because some problems that cause their basic intellegence is not able to develop. It is called underachiever students. Hopefully the shift of students learning skill pattern could improve underachiver students based on their intellegence. Hopefully the use of Wdep System as part of reality counseling is able to alterate better learning skill of underachiever students.This study used quasi experimental method. Six students ware taken as sample. The sample was taken by purposive sampling technique. The result showed that WDEP System is effetive to improve learning skill of underachiever students at the tenth class of Senior High School Yasmida Ambarawa in accademic year 2014/2015.Keywords: WDEP System, reality counseling, learning skill, underachiever students.